Pengaruh Jumlah Lubang pada Body Lori terhadap Perbandingan Oil Losses in Empty Bunch dan Oil in Condensate - Istianto Budhi Rahardja; Ahdiat Leksi Siregar; Siti Purwani (JURNAL CITRA WIDYA EDUKASI, 2019)
Palm Oil Mill (PKS) there are oil losses that cannot be eliminated, but it can be minimized, among them are the oil losses in empty bunch and the oil in condensate. The standardization of oil losses in empty bunch in POM is ≤ 2.25% (oil/wet matter), while the standardization of oil in condensate is ≤ 1% (oil/wet matter). The relationship of oil content contained in the empty bunch to condensate is due to the influence of holes in the body of the buggy. Thus, trials were carried out on two buggy units in the POM, ie buggy with 461 holes and 572 holes. The purpose of this research was to determine the value of the ratio of oil losses in empty bunch to the two buggy design. This research was conducted on May 27th – 29th, 2018. Data collection using literature study and observation method. The result showed that the buggy with in 461 holes resulted in 2.58% oil loss in empty bunch, more than the buggy with in 572 holes, ie 2.00%; and conversely, the buggy with in 572 holes resulted 1.05% oil in condensate, more than the buggy with in 461 holes, ie 0.88% only.